Digital balance and parental controls on mobile devices - Kopczyński, Tomasz (EDUsfera. Ewa Jurczyk-Romanowska, 2020)
The article aims to present the phenomenon of digital dementia in the context of measures aimed at minimising this phenomenon through digital balance measures, which are increasingly available in standard Android overlays. In addition, the article provides an overview of measures available in the form of software, and applications for mobile devices running on Android, which will allow for better monitoring control by parents in terms management of their children’s screen time
Keywords: digital balance; digital dementia; mobile devices; parental control